Personal Taxation and Portfolio Composition: An Econometric Analysis - Feldstein, Martin (Econometrica, 1976)
[Although the theory of taxation and portfolio choice has been extensively developed, the current paper begins the econometric study of this subject. The research analyzes the composition of portfolios of 1,799 households in a sample in which high income individuals are greatly overrepresented. The results show that the personal income tax has a very powerful effect on individuals' demands for portfolio assets after adjusting for the effects of net worth, age, sex, and the ratio of human to nonhuman capital.]